Gambaran College Adjustment Pada Mahasiswa Angkatan 2020 - Herdiansyah, Rido; Rahmi, Fitria; Sari, Liliyana (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2021)
University students are required to adjust to a different learning system from schools. The differences would made students experience difficulties, and this situation have been worsen with the COVID-19 pandemic that demanded a shift to full online learning. The purpose of this study was to describe college adjustment among university students, specifically class of 2020 which became the first class to experience full online learning when entering the college. The study used the descriptive quantitative method. A total of 380 Andalas University students in the class of 2020 was recruited through convenience sampling. The research instrument was the Student Adaptation to College Questionnaire (SACQ) developed by Baker & Syrik (1984) modified from Rohmah (2017). The results showed that college adjustment of university students was classified as high (68,42%). It shows that students generally have had effective behaviors in dealing with demands in the academic and social aspects, feel satisfied in college life, and have an attachment to the campus.